Development of Augmented Reality-Based Digital Learning Media for Grade V Elementary School on the Topic of Food Chains - Milda Qothruntina Istmadelia; Dewi Nilam Tyas (Jurnal Penelitian Pendidikan IPA, 2024)
This research focuses on developing Augmented Reality (AR)-based digital learning media to enhance the learning outcomes. The research follows the Research and Development (R&D) model with the ADDIE development approach, aiming to create learning media that can improve students' learning outcomes in the topic of food chains. The material validation scored 89.5, while the media validation scored 87.5, indicating that the media is deemed suitable for use. The normality test on a large scale yielded results of 0.99 and 0.21, signifying normal data distribution. Furthermore, the t-test results on a small scale were 0.00, and the N-Gain test on a large scale scored 71%. The normality test on a small scale yielded results of 0.55 and 0.42, indicating normal data distribution. The t-test on a small scale resulted in 0.01, and the N-Gain test on a small scale scored 84%, categorizing the effectiveness of Augmented Reality-based digital learning media on the topic of food chains as moderate. Based on the research findings, it can be concluded that an effective AR-based digital learning media on the topic of food chains has been successfully created to enhance the learning outcomes of fifth-grade students at Kasepuhan 02 Elementary School in Batang.